Listen to the world around us - Losleben, Lisa Katrin; Clerici, Monica; Holm, Villads; Panieri, Giuliana (Septentrio Educational, 2023)
Focus: To take time to identify and recognize the sounds in the spaces around us. Learning objectives: With this activity, we will draw attention to our surrounding environment through listening. This can function as a stand-alone activity. However, you can also use it as a starting point before transferring the experience to deep- sea environments in the activity called “Cold Seeps Symphony”. Key words: Spatial awareness, listening, sound walk, noise pollution.